Early-childhood exposure to per- and polyfluoroalkyl substances (PFAS) and neurobehavioral development in children - Chia-Jung Tung; Jia-Hwa Yang; Ching-Chun Lin; Chia-Yang Chen; Wu-Shiun Hsieh; Mei-Huei Chen; Pau-Chung Chen (Environmental Research, 2026)

Melatonin suppresses glycolysis and coordinately disrupts DNA repair via targeting the YAP1-NAMPT signaling in breast cancer - Yi-Wen Lai; Cheng-Ying Chu; Zei-Wei Liu; Hsin-Ying Lu; Chi-Ching Lee; Mei-Hsiang Lin; Cheng-Wei Lin (Chemico-Biological Interactions, 2026)

Correction to: Determination of critical power in trained rowers using a three-minute all-out rowing test - Ching-Feng Cheng; Yi-Shan Yang; Hui-Mei Lin; Chia-Lun Lee; Chun-Yi Wang (European Journal of Applied Physiology, 2026)

Optical properties of dissolved organic matter play pivotal roles in mediating trace metal forms in a mangrove-dominated tidal estuary - Keisuke Nakayama; Meng-Chi Hung; Chih-Yu Chiu; Sen-Lin Tang; Mei-Li Hsueh; Chin-Ching Wu; I-Hao Hung; Ya-Hsin Liu; Jeng-Wei Tsai (Marine Pollution Bulletin, 2026)

Dibifree, a dietary phytomix, improves glycemic control and adiposity via modulation of the gut–pancreas–adipose–immune axis in type 2 diabetes - Tzu-Yi Huang; Niann-Tzyy Dai; Hsiu-Jung Liao; Ly Hien Doan; Tai-Shan Cheng; Wen-Yu Hsieh; I-Hsuan Lin; Yu-Tang Huang; Chia-Ching Liaw; Hsiao-Sheng Liu; Wei-Ming Cheng; Chun-Li Su; et al. (Food Research International, 2026)

Associations between parental shift work exposure and pregnancy outcomes: role of father’s shift work status - Chih-Fu Wei; Mei-Huei Chen; Ching-Chun Lin; Yueliang Leon Guo; Shio-Jean Lin; Ya-Wen Chen; Wu-Shiun Hsieh; Pau-Chung Chen (International Archives of Occupational and Environmental Health, 2025)

Optimization formulation of Rhodiola rosea L. nanoemulsion containing natural oil using response surface method (RSM): preparation, characterization, stability test and antioxidant activity - Benni Iskandar; Hsiu-Mei Lin; Ching-Kuo Lee (Phytochemistry Letters, 2025)

Fabrication of superwetting gelatin/phytic acid/cellulose composites with antibacterial characteristics for separating complex contaminants from wastewater - Guyita Berako Belachew; Chien-Chieh Hu; Chih-Feng Wang; Mei-Yi Liao; Wei-Song Hung; Ching-Hsuan Lin; Shiao-Wei Kuo; Juin-Yih Lai (Journal of Water Process Engineering, 2025)

A comprehensive review of the functionalized polymer composite membranes in wastewater treatment - Madhappan Santhamoorthy; Perumal Asaithambi; Ilaiyaraja Perumal; Natarajan Elangovan; Priyadarshini Natarajan; Mei-Ching Lin; Seong-Cheol Kim; Keerthika Kumarasamy; Thi Tuong Vy Phan (Journal of Environmental Chemical Engineering, 2025)

Retraction notice to “Synthesis and characterization of Hypsizygus ulmarius extract mediated silver nanoparticles (AgNPs) and test their potentiality on antimicrobial and anticancer effects” [Environ. Res. 235 (2023) 116671] - Kumar Manimaran; Dede Heri Yuli Yanto; Sita Heris Anita; Oktan Dwi Nurhayat; Kumar Selvaraj; Santhosh Basavarajappa; Mohamed Ibrahim Hashem; Govindasamy Palanisamy; Mei-Ching Lin; Keerthika Kumarasamy (Environmental Research, 2025)

Pixel array-based urine biosensor for detection of trimethylamine N-oxide and glucose for early detection of diabetic kidney disease - Mei-Ching Yu; Chi-Jen Lo; Wei-Cheng Lin; Wei-Lun Yen; Yun-Yu Hsieh; Bing-Hong Chen; Fu-Sung Lo (Analytica Chimica Acta, 2025)

Rapid evaluation of apigenin bioavailability and hypouricemic bioactivity by targeted metabolomics study in enterohepatic microenvironment mimetic cell culture model - Su-Jung Hsu; Hui-Chen Chung; Chia-Hsuan Chang; Yi-Chi Liao; Ta-Wei Liu; Shu-Mei Lin; Ching-Kuo Lee (Food Research International, 2025)

Using Gaussian Mixture Model Clustering for the Automated Segmentation of Cerebral Arteriovenous Malformations in Magnetic Resonance Images - Ting-Yu Lin; Cheng‑Chia Lee; Yu-Wei Chen; Hsiu-Mei Wu; Ching-Jen Chen; Huai-Che Yang; Syu-Jyun Peng (Journal of Medical and Biological Engineering, 2025)

A ratiometric turn-on chemosensor for highly selective and sensitive visual detection of Zn2+ and its applications to environmental samples - Keerthika Kumarasamy; Zhe-Wei Wu; Wei-Jyun Chien; Mei-Ching Lin; Selva Kumar Ramasamy (Journal of Environmental Chemical Engineering, 2024)

Rational design of stable Cu and AuCu nanoparticles for investigations of size-enhanced SERS applications - Kuan-Wen Liu; Pei-Yu Sie; Jing-Yin Huang; Hsi-Ying Chen; Yi-Lun Chen; Yu-Ching Lin; Mei-Yi Liao (Analytica Chimica Acta, 2024)

Mitigating thermal burden and enhancing minor phase emission energy transfer in perovskite by introducing dopamine-mediated silver nanoparticles - Zhen-Li Yan; Jhih-Yuan Chang; Chieh Tsao; Meng-Xiu Fang; Bi-Hsuan Lin; Jia-Hau Tsai; Mei-Hsin Chen; Ru-Jong Jeng; Chi-Ching Kuo (Chemical Engineering Journal, 2024)

Dimercaprol-modified mesoporous silica nanoparticles for efficient removal of toxic mercury ions from aqueous solution - Madhappan Santhamoorthy; Suresh Ranganathan; Lesly Fathima Arul Sigamani; Seong-Cheol Kim; Saravanan Pandiaraj; Salim Manoharadas; Mei-Ching Lin; Keerthika Kumarasamy; Thi Tuong Vy Phan (Environmental Geochemistry and Health, 2024)

Synthesis of bis(2-aminoethyl)amine functionalized mesoporous silica (SBA-15) adsorbent for selective adsorption of Pb2+ ions from wastewater - Kokila Thirupathi; Madhappan Santhamoorthy; Ranganathan Suresh; Mohammad Ahmad Wadaan; Mei-Ching Lin; Seong-Cheol Kim; Keerthika Kumarasamy; Thi Tuong Vy Phan (Environmental Geochemistry and Health, 2024)

RETRACTED: Synthesis and characterization of Hypsizygus ulmarius extract mediated silver nanoparticles (AgNPs) and test their potentiality on antimicrobial and anticancer effects - Kumar Manimaran; Dede Heri Yuli Yanto; Sita Heris Anita; Oktan Dwi Nurhayat; Kumar Selvaraj; Santhosh Basavarajappa; Mohamed Ibrahim Hashem; Govindasamy Palanisamy; Mei-Ching Lin; Keerthika Kumarasamy (Environmental Research, 2023)

Phylogenetic divergence associated with climate oscillations and topology illustrates the dispersal history of Formosan sambar deer (Rusa unicolor swinhoii) in Taiwan - Kuan-Yi Li; Chen Hsiao; Shih-Ching Yen; Chien-Yi Hung; You-Zhu Lin; Sheng-Wun Jheng; Pei-Ju Yu; Mei-Hsiu Hwang; Guo-Jing Weng; Ku-Lin Chen; Shu-Fen Lin; Shih-Wei Chang; et al. (Mammal Research, 2023)
The island of Taiwan represents an ideal context for studying the effects of climatic oscillations and topographic variation on large herbivores due to its varied tropical to sub-tropical climate zones at different elevational ranges. We explored the phylogenetics of Formosan sambar deer ( Rusa unicolor swinhoii ) using the control region of the mitochondrial genome. We detected 18 haplotypes among 454 sequences across the island and grouped them into six regions based on SAMOVA, with 68.78% variance among regions. A Bayesian phylogenetic dendrogram revealed two spatially segregated genetic clades. Neutrality tests and Bayesian skyline plots uncovered different demographic expansion histories for the two clades. We further tested divergence times and chronology to propose potential phylogenetic scenarios, which were examined using approximate Bayesian computation. Finally, we present a credible hypothesis for a glacial refugium in the northern part of the Central Mountain Range. Subsequent secondary contact between the two clades during interglacial periods has led to the extant genetic structure of Formosan sambar deer.

Sleep disturbance in adults with untreated primary brain tumors: prevalence and impact on quality of life - Pei-Ching Lin; Pin-Yuan Chen; Kuo-Chen Wei; Jian-her Lin; Mei-Ru Lin; Huan-Chih Wang; Hsiao-Yean Chiu (Sleep and Biological Rhythms, 2023)

Identification of serum metabolic signatures of environmental-leveled phthalate in the Taiwanese child population using NMR-based metabolomics - Sheng-Han Lee; Zhi-Yi Du; Wei-Chen Tseng; Wan-Yu Lin; Mei-Huei Chen; Ching-Chun Lin; Hao-Jan Liang; Hui-Ju Wen; Yue-Leon Guo; Pau-Chung Chen; Ching-Yu Lin (Environmental Pollution, 2023)

Targeting Inflammation, PHA-767491 Shows a Broad Spectrum in Protein Aggregation Diseases - Yu-Han Chung; Chia-Wei Lin; Hsin-Yu Huang; Shu-Ling Chen; Hei-Jen Huang; Ying-Chieh Sun; Guan-Chiun Lee; Guey-Jen Lee-Chen; Ya-Ching Chang; Hsiu Mei Hsieh-Li (Journal of Molecular Neuroscience, 2020)

Population Structure of the World Vegetable Center Mungbean Mini Core Collection and Genome-Wide Association Mapping of Loci Associated with Variation of Seed Coat Luster - Caleb Manamik Breria; Ching Hsiang Hsieh; Jo-Yi Yen; Ramakrishnan Nair; Chen-Yu Lin; Shu-Mei Huang; Thomas J. Noble; Roland Schafleitner (Tropical Plant Biology, 2020)

Twist1 Plays an Anti-apoptotic Role in Mutant Huntingtin Expression Striatal Progenitor Cells - Wei-Ping Jen; Hui-Mei Chen; Yow-Sien Lin; Yijuang Chern; Yi-Ching Lee (Molecular Neurobiology, 2020)

Comparative Study of Regulations of Devices for Aesthetic Purposes: US, European Union, China, and Taiwan - Mei-Fen Chen; Cheng-Lun Tsai; Yung-Hsin Chen; Cheng-Ning Wu; Ching Chou; Chia-Hung Chien; Pei-Weng Tu; Tsair Kao; Kang-Ping Lin (Journal of Medical and Biological Engineering, 2020)

Progressive multifocal leukoencephalopathy in a renal transplant patient - Tsu-Chen Lin; Mei-Yi Wu; Hui-Tzung Luh; Shiou-Fu Lin; Chien-Min Lin; Ying-Chi Tseng; Yung-Ching Liu; Mai-Szu Wu (Journal of NeuroVirology, 2019)

Modeling Alzheimer’s Disease by Induced Pluripotent Stem Cells Carrying APP D678H Mutation - Kuo-Hsuan Chang; Guey-Jen Lee-Chen; Ching-Chang Huang; Jia-Li Lin; Yi-Jing Chen; Pei-Chi Wei; Yen-Shi Lo; Chin-Fa Yao; Ming-Wei Kuo; Chiung-Mei Chen (Molecular Neurobiology, 2019)

Adenosine Augmentation Evoked by an ENT1 Inhibitor Improves Memory Impairment and Neuronal Plasticity in the APP/PS1 Mouse Model of Alzheimer’s Disease - Chia-Chia Lee; Ching-Pang Chang; Chun-Jung Lin; Hsing-Lin Lai; Yu-Han Kao; Sin-Jhong Cheng; Hui-Mei Chen; Yu-Ping Liao; Emilie Faivre; Luc Buée; David Blum; Jim-Min Fang; et al. (Molecular Neurobiology, 2018)

Web-Based Experience Sharing Platform on Medical Device Incidents for Clinical Engineers in Hospitals - Mei-Fen Chen; Cheng-Lun Tsai; Yung-Hsin Chen; Yu-Wen Huang; Cheng-Ning Wu; Ching Chou; Chia-Hung Chien; Pei-Weng Tu; Tsair Kao; Kang-Ping Lin (Journal of Medical and Biological Engineering, 2018)

Tamoxifen usage correlates with increased risk of Parkinson’s disease in older women with breast cancer: a case–control study in Taiwan - Hsien-Feng Lin; Kuan-Fu Liao; Ching-Mei Chang; Cheng-Li Lin; Shih-Wei Lai (European Journal of Clinical Pharmacology, 2018)

Association of use of selective serotonin reuptake inhibitors with risk of acute pancreatitis: a case-control study in Taiwan - Hsien-Feng Lin; Kuan-Fu Liao; Ching-Mei Chang; Cheng-Li Lin; Shih-Wei Lai (European Journal of Clinical Pharmacology, 2017)

Correlation between proton pump inhibitors and risk of pyogenic liver abscess - Hsien-Feng Lin; Kuan-Fu Liao; Ching-Mei Chang; Cheng-Li Lin; Shih-Wei Lai (European Journal of Clinical Pharmacology, 2017)

The potential of the brown seaweed Sargassum polycystum against acne vulgaris - Jamie Mei-Lin Kok; Jap-Meng Jee; Lye-Yee Chew; Ching-Lee Wong (Journal of Applied Phycology, 2016)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

Methodology of disaster risk assessment for debris flows in a river basin - Ing-Jia Chiou; Ching-Ho Chen; Wei-Lin Liu; Shiao-Mei Huang; Yu-Min Chang (Stochastic Environmental Research and Risk Assessment, 2015)

Association Study Between Macrophage Migration Inhibitory Factor-173 Polymorphism and Acute Myeloid Leukemia in Taiwan - Latha Ramireddy; Chien-Yu Lin; Su-Ching Liu; Wan-Yu Lo; Rouh-Mei Hu; Yi-Chin Peng; Ching-Tien Peng (Cell Biochemistry and Biophysics, 2014)

Development of transgenic watermelon resistant to Cucumber mosaic virus and Watermelon mosaic virus by using a single chimeric transgene construct - Ching-Yi Lin; Hsin-Mei Ku; Yi-Hua Chiang; Hsiu-Yin Ho; Tsong-Ann Yu; Fuh-Jyh Jan (Transgenic Research, 2012)

Coexisting mutations/polymorphisms of the long QT syndrome genes in patients with repaired Tetralogy of Fallot are associated with the risks of life-threatening events - Shuenn-Nan Chiu; Mei-Hwan Wu; Ming-Jai Su; Jou-Kou Wang; Ming-Tai Lin; Chien-Chih Chang; Hui-Wen Hsu; Ching-Tsuen Shen; Olivier Thériault; Mohamed Chahine (Human Genetics, 2012)

Determination of critical power in trained rowers using a three-minute all-out rowing test - Ching-Feng Cheng; Yi-Shan Yang; Hui-Mei Lin; Chia-Lun Lee; Chun-Yi Wang (European Journal of Applied Physiology, 2012)

Evaluation of DNA fragments covering the entire genome of a monopartite begomovirus for induction of viral resistance in transgenic plants via gene silencing - Ching-Yi Lin; Wen-Shi Tsai; Hsin-Mei Ku; Fuh-Jyh Jan (Transgenic Research, 2012)

Transcriptional analysis and functional characterization of XCC1294 gene encoding a GGDEF domain protein in Xanthomonas campestris pv. campestris - Yi-Min Hsiao; Wan-Ling Song; Chao-Tsai Liao; I-Hsuan Lin; Mei-Ying Pan; Ching-Fen Lin (Archives of Microbiology, 2012)

An easy and efficient protocol in the production of pflp transgenic banana against Fusarium wilt - Mei-Kuen Yip; Sin-Wan Lee; Kuei-Ching Su; Yi-Hsien Lin; Tai-Yang Chen; Teng-Yung Feng (Plant Biotechnology Reports, 2011)

Analysis of genetic variations in the dopamine D1 receptor (DRD1) gene and antipsychotics-induced tardive dyskinesia in schizophrenia - I-Ching Lai; Geng-Han Mo; Mao-Liang Chen; Ying-Chieh Wang; Jen-Yeu Chen; Ding-Lieh Liao; Ya-Mei Bai; Chao-Cheng Lin; Tzu-Ting Chen; Ying-Jay Liou (European Journal of Clinical Pharmacology, 2011)

Resistance to a DNA and a RNA virus in transgenic plants by using a single chimeric transgene construct - Ching-Yi Lin; Hsin-Mei Ku; Wen-Shi Tsai; Sylvia K. Green; Fuh-Jyh Jan (Transgenic Research, 2011)

Association between human papillomavirus and adenocarcinoma of rectum and recto-sigmoid junction: a cohort study of 10,612 women in Taiwan - Li-Chung Chuang; Hui-Chi Chen; San-Lin You; Ching-Yu Lin; Mei-Hung Pan; Yi-Chun Chou; Chang-Yao Hsieh; Chien-Jen Chen (Cancer Causes & Control, 2010)

Constitutive expression of a fungal glucose oxidase gene in transgenic tobacco confers chilling tolerance through the activation of antioxidative defence system - Subbiyan Maruthasalam; Yi Lun Liu; Ching Mei Sun; Pei Ying Chen; Chih Wen Yu; Pei Fang Lee; Chin Ho Lin (Plant Cell Reports, 2010)

Involvement of the residues of GSKIP, AxinGID, and FRATtide in their binding with GSK3β to unravel a novel C-terminal scaffold-binding region - Shen-Long Howng; Chi-Ching Hwang; Chia-Yi Hsu; Meng-Yu Hsu; Chun-Yen Teng; Chia-Hua Chou; Mei-Feng Lee; Chia-Hung Wu; Shean-Jaw Chiou; Ann-Shung Lieu; Joon-Khim Loh; Chia-Ning Yang; et al. (Molecular and Cellular Biochemistry, 2010)

Erratum to: Novel mutations in the connexin43 (GJA1) and GJA1 pseudogene may contribute to nonsyndromic hearing loss - Hui-Mei Hong; Jiann-Jou Yang; Jia-Ching Shieh; Mei-Ling Lin; Shuan-Yow Li (Human Genetics, 2010)

Development of a molecular marker for a bruchid (Callosobruchus chinensis L.) resistance gene in mungbean - Huei-Mei Chen; Chien-An Liu; C. George Kuo; Ching-Mei Chien; Horng-Chi Sun; Chung-Chu Huang; Yu-Chung Lin; Hsin-Mei Ku (Euphytica, 2007)

Effects of cardiotoxin III on expression of genes and proteins related to G2/M arrest and apoptosis in K562 cells - Sheng-Huei Yang; Chien-Hsun Tsai; Mei-Chin Lu; Yung-Ning Yang; Ching-Ming Chien; Sheng-Fung Lin; Shinne-Ren Lin (Molecular and Cellular Biochemistry, 2007)

A fine physical map of the rice chromosome 5 - Chia-Hsiung Cheng; Mei-Chu Chung; Shu-Mei Liu; Shi-Kuang Chen; Fang-Yi Kao; Shu-Jen Lin; Shin-Hsin Hsiao; I-Chieh Tseng; Yue-Ie C. Hsing; Hong-Pang Wu; Ching-San Chen; Jei-Fu Shaw; et al. (Molecular Genetics and Genomics, 2005)

Transgenic tomato plants expressing the Arabidopsis NPR1 gene display enhanced resistance to a spectrum of fungal and bacterial diseases - Wan-Chi Lin; Ching-Fang Lu; Jia-Wei Wu; Ming-Lung Cheng; Yu-Mei Lin; Ning-Sun Yang; Lowell Black; Sylvia K. Green; Jaw-Fen Wang; Chiu-Ping Cheng (Transgenic Research, 2004)